2017
DOI: 10.1016/j.bjm.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature ethanol production using thermotolerant yeast newly isolated from Greater Mekong Subregion

Abstract: The application of high-potential thermotolerant yeasts is a key factor for successful ethanol production at high temperatures. Two hundred and thirty-four yeast isolates from Greater Mekong Subregion (GMS) countries, i.e., Thailand, The Lao People's Democratic Republic (Lao PDR) and Vietnam were obtained. Five thermotolerant yeasts, designated Saccharomyces cerevisiae KKU-VN8, KKU-VN20, and KKU-VN27, Pichia kudriavzevii KKU-TH33 and P. kudriavzevii KKU-TH43, demonstrated high temperature and ethanol tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 60 publications
11
41
0
1
Order By: Relevance
“…104,105 Thus, a more thermotolerant yeast could improve the efficiency of this step. 106 To discover whether certain encapsulation matrices offer more protection against thermal stress than others, yeast were subjected to heat shock at 50 C for 180 min. Planktonic cells, in either exponential or stationary phase, as well as cells encapsulated in each of four matrices, were exposed to 50 C for 5, 15, 30, 90, and 180 min ( Figure 6), after which viability was assessed as CFUs following dilution and plating on rich agar.…”
Section: Cell Viability Declined Over Time In Both Encapsulated Andmentioning
confidence: 99%
See 1 more Smart Citation
“…104,105 Thus, a more thermotolerant yeast could improve the efficiency of this step. 106 To discover whether certain encapsulation matrices offer more protection against thermal stress than others, yeast were subjected to heat shock at 50 C for 180 min. Planktonic cells, in either exponential or stationary phase, as well as cells encapsulated in each of four matrices, were exposed to 50 C for 5, 15, 30, 90, and 180 min ( Figure 6), after which viability was assessed as CFUs following dilution and plating on rich agar.…”
Section: Cell Viability Declined Over Time In Both Encapsulated Andmentioning
confidence: 99%
“…,105 Thus, a more thermotolerant yeast could improve the efficiency of this step 106,107. Moreover, since cooling costs for fermentation tanks can be costly in the summer, especially in warmer regions, 108 a more thermotolerant yeast could also help reduce cooling costs, and is thus doubly favored.…”
mentioning
confidence: 99%
“…2) in this study. Such discrepancy in ethanol concentrations might result from genetic variability, differences in inoculum concentration or chemistry of the feedstock (Techaparin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Auesukaree et al [51] reported a strain C3867 that produced 38.8 g/L of ethanol at 41°C. Recently, Nuanpeng et al [52] and Techaparin et al [53] isolated S. cerevisiae DBKKUY-53 and KKU-VN8, respectively, in Thailand. The former strain produced the maximum ethanol concentration and volumetric ethanol productivity of 85.0 g/L and 2.83 g/L h, respectively, at 40°C, and the latter strain produced the maximum ethanol concentration of 89.3 g/L with a productivity of 2.48 g/L h and a theoretical ethanol yield of 96.3% from sweet sorghum juice at 40°C.…”
Section: Various Ethanologenic Thermotolerant Yeasts and Their Characmentioning
confidence: 99%